Comparing The Content Of The Iraqi Mathematics Book With The Saudi Mathematics Book For The Third Intermediate Grade And The Availability Of 21St Century Skills In The Iraqi Book - Mohsen Hamad, Salwa (Opción, 2019)
Mathematics curricula represent an important curriculum that most coun- tries seek to develop and modernize, in order to meet the recent developments and changes in the twenty-first century, and it is appropriate that the curric- ulum of mathematics to keep pace with this change and keep pace, and must take off the traditional math, and must be updated and developed to achieve its goals , And keep pace with the requirements of the times of scientific and technological innovations, especially as the age in which we live is charac- terized by rapid changes in all aspects of life. In this age of knowledge is no longer defined, change has many manifestations, the most important of which is the revolution of knowledge and the explosion of knowledge, which in turn affects the curriculum, can not imagine the existence of a consistent curric- ulum in a permanent and rapidly changing era, which urged educators to conduct development and change of the curriculum, to keep pace Tremendous cognitive progress in all fields (Salem, 2008: 18), and the rapid development of life and conditions in the twenty-first century from what it was in the last century, made it necessary to develop curricula to cope with the remarkable transformation in all areas of life, where we must add New skills keep pace with this development By adding components into the curriculum and peda- gogical practices to help students develop future work environments, such as collaboration, communication, problem solving, and information dissemina- tion (Al-Ghamdi and Khalid, 2015: 4), the technological revolution poses an important challenge: With high abilities in the use of mathematics, comput- er literacy, problem solving, and decision-making (Rafael and Mohammed, 2001: 20), one of these challenges is the availability of 21st century skills in our curriculum, and the training of students to keep pace with oth- er countries and curricula in development, To catch up Wheel evolution.